Infant-directed speech as a simplified but not simple register: a longitudinal study of lexical and syntactic features. Issue 1 (30th January 2020) - GENOVESE, Giuliana; SPINELLI, Maria; ROMERO LAURO, Leonor J.; AURELI, Tiziana; CASTELLETTI, Giulia; FASOLO, Mirco
Abstract: Infant-directed speech (IDS) is a specific register that adults use to address infants, and it is characterised by prosodic exaggeration and lexical and syntactic simplification. Several authors have underlined that this simplified speech becomes more complex according to the infant's age. However, there is a lack of studies on lexical and syntactic modifications in Italian IDS during the first year of an infant's life. In the present study, 80 mother–infant dyads were longitudinally observed at 3, 6, 9, and 12 months during free-play interactions. Maternal vocal productions were subsequently coded. The results show an overall low lexical variability and syntactic complexity that identify speech to infants as a simplified register; however, the high occurrence of complex items and well-structured utterances suggests that IDS is not simple speech. Moreover, maternal IDS becomes more complex over time, but not linearly, with a maximum simplification in the second half of the first year.